2016
DOI: 10.1073/pnas.1603079113
|View full text |Cite
|
Sign up to set email alerts
|

Direct and essential function for Hrd3 in ER-associated degradation

Abstract: The HRD (HMG-CoA reductase degradation) pathway is a conserved route of endoplasmic reticulum-associated degradation (ERAD), by which misfolded ER proteins are ubiquitinated and degraded. ERAD substrates are ubiquitinated by the action of the Hrd1 RING-H2 E3 ligase. Hrd1 is always present in a stoichiometric complex with the ER membrane protein Hrd3, which is also required for HRD-dependent degradation. Despite its conserved presence, unequivocal study of Hrd3 function has been precluded by its central role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 26 publications
1
55
0
Order By: Relevance
“…Recently, Hampton and his colleagues succeeded in the stabilization of Hrd1p in the absence of Hrd3p by simultaneously deleting the UBL domain of Usa1p (yeast homologue of Herp1/2), which is required for autodegradation of Hrd1p in the absence of Hrd3p (Vashistha et al, 2016). Using this Usa1p-ΔUBL/ΔHrd3p strain they showed that Hrd3p is required for ubiquitination of ERAD substrate by Hrd1p.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hampton and his colleagues succeeded in the stabilization of Hrd1p in the absence of Hrd3p by simultaneously deleting the UBL domain of Usa1p (yeast homologue of Herp1/2), which is required for autodegradation of Hrd1p in the absence of Hrd3p (Vashistha et al, 2016). Using this Usa1p-ΔUBL/ΔHrd3p strain they showed that Hrd3p is required for ubiquitination of ERAD substrate by Hrd1p.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it was difficult to study the role of Hrd3 in ERAD due to the increased turnover of Hrd1 when HRD3 is deleted. However, when the ubiquitin-like domain of Usa1 is removed, Hrd1 remains stable and a direct role for Hrd3 in ERAD was established [106]. Der1 also binds soluble luminal substrates and interacts with Hrd1 through Usa1 [107, 108].…”
Section: Expanding the Links Between Ubiquitination And Eradmentioning
confidence: 99%
“…Regulated ubiquitination of HMGR was first discovered and studied in S. cerevisiae (Hampton & Bhakta 1997, Hampton et al 1996), and its study continues to provide insights into both sterol regulation and ERAD (Neal et al 2017, Sato et al 2009, Vashistha et al 2016). HMGR is essential for life in yeast, allowing synthesis of many isoprenoids and ergosterol, which is the principal sterol.…”
Section: Regulated Degradation Of Hmg-coa Reductase In Saccharomyces mentioning
confidence: 99%
“…Genetic analysis of Hmg2 degradation led to the discovery of the HRD genes (which are responsible for H mg-CoA r eductase d egradation), along with many other substrates. The HRD1 and HRD3 genes encode a pair of ER-resident proteins that form the core subunits of a highly conserved E3 ubiquitin ligase, which is responsible for ubiquitination of Hmg2, leading to proteasome-mediated degradation (Bays et al 2001, Gardner et al 2000, Hampton & Garza 2009, Hampton et al 1996, Vashistha et al 2016). The Hrd1 protein is a multispanning E3 ubiquitin ligase with an N-terminal transmembrane region and a C-terminal E3 ubiquitin ligase domain.…”
Section: Regulated Degradation Of Hmg-coa Reductase In Saccharomyces mentioning
confidence: 99%